OPTIMASI PENGGUNAAN ADSORBEN KITOSAN 0,9% TERHADAP DAYA SERAP AMONIAK DALAM AIR LIMBAH KILANG MINYAK OUTLET IMPOUNDING BASIN (OIB) PERTAMINA RU VI BALONGAN, INDRAMAYU - Novritasari, Eksa; Sedjati, Sri; Yulianto, Bambang (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Products of petroleum of liquid waste can be caused pollution in the ocean. Waste contains of chemical element especially ammonia. High concentration of ammonia has toxicity for human and aquatic ecosystems. This Research was aimed to decrease concentration of ammonia by chitosan liquid. The research was conducted in Technological Laboratory of Pertamina RU VI Balongan Indramayu on March - April 2013. The Method of this research used randomized design with kind of treatments is 4 levels and 3 repetition. Treatments of this research used chitosan liquid 0,9% with different variation between chitosan liquid and sample of waste oil refinery, such as : (A) 4%; (B) 8%; (C)12%; (D)16%, with 30 minutes time contact. The largest decrease of ammonia contained in (C) 12% Â± 12,83 mg/L (48,67%) and optimum adsorption is 10,28 % Â± 13,87 mg/L (44,52%).